Cost issue: Key limiting factor that affects IBS application in Malaysian construction industry - Wong, Amy, Zhi Lin; Chan, Siew Chong (INTI International University, 2018)
In order to achieve the target of being a developing nation in Year 2020, Malaysian government has been investing its efforts in driving the nation to optimize the utility of new, modern and innovative construction methods, including Industrial Building System (IBS), however there are still a number of unresolved issues arisen. Thus, the objectives of this paper are to identify the Cost and Non-cost Factors related to IBS; and further, to justify the significance of Cost Factors in influencing IBS application. Questionnaires were distributed to targeted 44 respondents who consisted of contractors and suppliers. The data were tabulated and further analyzed using Descriptive Statistics and Hypothesis Testing. The findings of the research show the Cost Factors do play significant roles in affecting the extent of IBS application in Malaysian construction industry. Thus, the related parties are needed to look into the possible areas of improving the application of IBS through reducing the rates of design and construction costs.